Managing Conflicts with Wildlife: Living with Alligators - Steve A. Johnson; Harry Dutton; Alan Woodward; William Giuliano; Holly Ober (EDIS)
As one of the largest reptiles in North America, alligators are situated at the top of the food chain. In general, alligators do not pose a threat to people. However, alligators can pose potential dangers to people in some situations. In this publication, we present some facts about alligators, describe their potential threats to people and pets, and provide suggestions on how to cope with these risks. Our target audience includes anyone living in or visiting the geographic range of American alligators.